Upconversion nanoparticles loaded with eIF4E siRNA and platinum(iv) prodrug to sensitize platinum based chemotherapy for laryngeal cancer and bioimaging. Issue 2 (9th December 2016) - Teng, Bo; Ma, Ping'an; Yu, Chang; Zhang, Xinyang; Feng, Qingjie; Wen, Lianji; Li, Chunxia; Cheng, Ziyong; Jin, Dayong; Lin, Jun
Abstract : Eukaryotic translation initiation factor (eIF) 4E is a valuable marker in cancer prognostics in many human cancers. Abstract : Eukaryotic translation initiation factor (eIF) 4E is a valuable marker in cancer prognostics in many human cancers. Silencing eIF4E via delivery of siRNA may be able to overcome chemoresistance. Cisplatin, used as a first-line anti-cancer reagent, has been widely accepted for its great success in clinical applications but it is restricted due to severe side effects such as nephrotoxicity, peripheral neuropathy, and hearing loss. Moreover, platinum drug resistance is a major obstacle to its use. Platinum(iv ) prodrugs (denoted as Pt(iv )) which could be reduced to Pt(ii ) by various reductants, including mercaptan and glutathione, within cancer cells have very limited toxicity and might overcome platinum resistance because of their chemical inertness. Moreover, combinational therapies that could sensitize the cancer cells to Pt drugs have received great attention nowadays around the world. Here we report a simple and effective upconversion nanoparticle carrier system loaded with both eIF4E siRNA and Pt(iv ). We find that this theranostic system could sensitize laryngeal cancer cells to cisplatin based chemotherapy and allow bioimaging both in vitro and in vivo .